Improved performance of InGaN/GaN flip-chip light-emitting diodes through the use of robust Ni/Ag/TiW mirror contacts - Hasanov, Namig (2018)
In this work, the authors report the incorporation of TiW alloy in InGaN/GaN-based flip-chip light-emitting diodes (LEDs). The advantages provided by the use of TiW are analyzed in detail. InGaN/GaN multiple quantum well LEDs with a Ni/Ag/TiW metal stack are found to tolerate high-temperature annealing better than those with a Ni/Ag metal stack. Highly improved current–voltage characteristics and enhanced optical output power are achieved for the devices with a TiW thin layer. These changes are ascribed to the higher reflectivity, smoother surface, and better ohmic properties of the device containing TiW after annealing. Better heat management of the device with TiW is demonstrated by comparing electroluminescence spectra of the two device structures. Overall, these factors resulted in devices with TiW exhibiting a higher external quantum efficiency than devices without TiW. Detailed x-ray photoelectron spectroscopy analyses of the reflector metal stacks reveal little intermixing of the layers after annealing in the devices with TiW. The results show that incorporation of TiW is a promising approach for the fabrication of high-performance InGaN/GaN flip-chip LEDs.